2021
DOI: 10.1016/j.mtbio.2021.100168
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-integrated colorimetric sensor array-based reader system and fluorometric detection of dopamine in male and female geriatric plasma by bluish-green fluorescent carbon quantum dots

Abstract: A simple, cost-effective system was developed for dopamine (DA) detection using green synthesized 1–6 ​nm honey-based carbon quantum dots (H-CQDs) exhibiting bluish green fluorescence. The H-CQDs exhibited emission at 445 ​nm, with a quantum yield of ∼44%. The H-CQDs were used as a probe for electron transfer based DA detection and changes in H-CQD color in the presence of DA. The H-CQDs were formed with polar functional groups and were highly soluble in aqueous media. In the fluorometric mode, the proposed sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Other sensoristic systems has been used by employing a smartphone as detector for DA sensing in real samples. In particular, DA has been detected in urine, with a linear response in the range of micromolar, and a limit of detection under micromolar concentration [ 8 , 32 ]; in plasma with a linear response in the range of nanomolar—micromolar and a detection limit of micromolar concentration [ 34 ]; and in sweat with a linear response up to millimolar concentration and a nanomolar limit of detection [ 31 ]. Our device, with a picomolar limit of detection and a linearity in the range 10 pM–10 μM, shows better results in these analytical parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sensoristic systems has been used by employing a smartphone as detector for DA sensing in real samples. In particular, DA has been detected in urine, with a linear response in the range of micromolar, and a limit of detection under micromolar concentration [ 8 , 32 ]; in plasma with a linear response in the range of nanomolar—micromolar and a detection limit of micromolar concentration [ 34 ]; and in sweat with a linear response up to millimolar concentration and a nanomolar limit of detection [ 31 ]. Our device, with a picomolar limit of detection and a linearity in the range 10 pM–10 μM, shows better results in these analytical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the use of a simple smartphone as detector leads to the possibility to a “homemade” DA levels detection. Few examples of smartphone-based methods able to determine the DA concentration, in micromolar ranges, have been reported [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In this context, the possibility to restore the starting sensor leads to the opportunity to reuse the device.…”
Section: Introductionmentioning
confidence: 99%
“…The peak located at 2882 cm −1 was shifted slightly to 2904 cm −1 due to alkyl C−H stretching [ 68 ]. The intensity of the observed peak around 1507 cm −1 was increased due to aromatic C=C stretching, and the peak located around 1287 cm −1 originated due to amine C–N stretching [ 68 , 69 ]. These findings confirmed the reaction between DA and CQD film and revealed that once DA was introduced, the functional groups of CQDs altered conformationally.…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine was recently recognized with higher sensibility by Yun and co-workers using CNPs obtained from honey. 77 In particular, the presence of dopamine led to a quenching of the emission due to the redox reaction between dopamine and CNP ( Fig. 9a ).…”
Section: Cnps For Chemical Sensingmentioning
confidence: 95%